SEMI-EXTENSIVE BEEF CATTLE BREEDING MANAGEMENT IN DOMPU REGENCY, WEST NUSA TENGGARA - Febri Ariyanti; M. Yandi Fadilah; Fatkhanuddin Aziz; Muhammad Rosyid Ridlo; Nurulia Hidayah; Nur Ika Prihanani; Ida Tjahajati; Fajar Budi Lestari; Morsid Andityas; Clara Ajeng Artdita (Buletin Veteriner Udayana, 2025)
Beef cattle farming in Dompu Regency, West Nusa Tenggara, is conducted semi-extensively for various purposes, including breeding. This study aimed to identify the beef cattle breeding management practices used by smallholder farmers in Dompu Regency. Data were collected through field observations and interviews using questionnaires administered to 133 farmers in two villages: Dorebara and Adu. The research variables included farmer characteristics, reproductive issues, preferred cattle breeds, breeding management, feeding practices, and livestock health control. The results showed that most farmers were of productive age, had completed secondary education, and operated their farms as a side business driven by economic and socio-religious motivations. The main challenges in semi-extensive beef cattle breeding were limited access to bulls, long calving intervals, and low body condition scores in cows. Farmers preferred Bali cattle and crossbred cattle, and continued to rely on natural mating because it is accessible and cost-effective. The use of legumes such as Leucaena leucocephala during pregnancy and lactation remains suboptimal, as knowledge of feed management is largely based on tradition. Livestock health programs have been supported by the government through annual vaccination campaigns, but farmers’ awareness of livestock health remains low. Beef cattle productivity in semi-extensive systems can be improved through technical assistance, extension services, and better access to superior bulls and high-quality forage.